Forest biomes
The complexity of the forest ecosystem is explored with live-action video in this fascinating multimedia presentation. Students will examine the coniferous forests of the world, as well as deciduous forest communities in the more temperate climates. They will study the intricate and delicately balanced network of plant and animal relationships that make up the food chain in these ecosystems. Finally, students will look at how the humid climate of the tropical rain forests supports plant and animals life that is much different, but equally rich and fascinating.